Mining the Watkins collection of wheat landraces for novel sources of eyespot resistance. (11th April 2014) - Burt, C.; Griffe, L. L.; Ridolfini, A. P.; Orford, S.; Griffiths, S.; Nicholson, P.
<x xml:space="preserve">Abstract</x> Eyespot is an economically important stem base disease of wheat caused by the soilborne fungal pathogens Oculimacula yallundae and Oculimacula acuformis. The most effective method of controlling the disease is host resistance. However, there are only three genetically characterized resistances in wheat varieties and further sources of resistance are required. Previous studies have identified resistances in wild relatives, but use of these resistances has been limited by linkage drag with deleterious traits exacerbated by low rates of recombination. Therefore, the identification of novel resistances in hexaploid wheat germplasm is desirable. The Watkins collection currently consists of 1056 hexaploid wheat landraces that represent global wheat diversity at the time of its collection in the 1920s and 1930s. As such, it may contain beneficial agronomic traits such as eyespot resistance. The Watkins collection was screened for resistance to O. yallundae based on a glasshouse test of all 1056 accessions and a polytunnel test of 44 accessions selected from a previous field trial. Resistant lines identified in these tests were retested against both O. yallundae and O. acuformis. This identified 17 accessions with resistance to one or both of the pathogen species. From these, two accessions (1190094.1 and 1190736.3) provided a high level of resistance to both pathogen species. An F4 population derived from accession 1190736.3 indicated that the resistance to O. acuformis in this accession is conferred by a single gene and therefore would be suitable for introgression into elite wheat varieties to provide an alternative source of eyespot resistance.